Pengembangan Instrumen Evaluasi Higher Order Thinking Skills Menggunakan Quizizz Pada Materi Termokimia untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi Peserta Didik - Lani Dwi Kurnia*; Sri Haryati; Roza Linda (Jurnal Pendidikan Sains Indonesia, 2022)
The ability of students in understanding complex information and analyzing skills is classified as low grade, therefore a HOTS-based evaluation instrument is needed using media that is able to develop high thinking skills and increase the enthusiasm of students doing evaluations. The purpose of this study is producing an evaluation instrument based on HOTS using Quizizz on a valid thermochemistry subject according to material and media experts, knowing the validity, reliability, difficulty level, distinguishing power and user responses. This research uses a research and development (R D) with the Plomp model. The research subjects are 3 teachers and 30 students of class XI of SMAN 8 Pekanbaru, SMAN 2 Pekanbaru and MAN 1 Pekanbaru. Data collection techniques are carried out by literature studies and field studies. The research data is obtained from the validation results of two material validators, two media validators, and user trials. The result of validation to material validators was obtained on the average based on material aspect of 95.83%, construction aspect 94.03% and language aspect 98.89%. According to media validators, based on content aspect of 89.00%, learning design 90.00%, display (visual communication) 89.00% and software utilization 95.00%. The results of the questions analysis showed that 12 questions qualified the valid criteria, had very high reliability, “medium” difficulty level of 5 questions and “difficult” category of 7 questions and had good distinguishing power with all questions accepted. User response scores are 90.67% by teachers and 93.13% by students with very good criteria